Effect of dust accumulation on the performance of photovoltaic panels in desert countries: A case study for Madinah, Saudi Arabia - Mohamed Benghanem; Abdullah Almohammedi; Mohammed Taukeer Khan; Ahmad Al-Masraqi (Institute of Advanced Engineering and Science, 2018)
The present research shows the effect of dust accumulation on the surface of photovoltaic (PV) modules, which cause losses in their output power. We got 28% of losses in output power at Madinah city during 60 days of dust accumulation. Two ways were used to study the effect of dust on the PV modules of type monocrystalline silicon: the quantitative and the qualitative approaches respectively. A model based on dust density is used to determine the losses of output PV power. We propose to add an important parameter noted dust accumulation coefficient (%/mg.cm-2), in data sheet of PV modules manufacturer. In addition, an intelligent cleaning system is proposed, using the notion of dust density, to start cleaning when an admissible value of power losses is reached. This process allows minimizing the effect of dust.